Product placement on UK television: Is the expenditure worth the outcome? - Joyce, Lydia (2013)
In recent years the size of the product placement industry has been growing, incorporating different types of media including film, television, video games and music videos. This presents a significant opportunity for marketers to promote their products in front of the increasingly technology savvy consumers who aim to ignore traditional advertising techniques.